Hybridization patterns and the evolution of reproductive isolation in ducks - Tubaro, Pablo Luis (2002)
Much of our knowledge of the evolution of reproductive isolation comes from studies of Drosophila. This body of work has revealed the following patterns: (1) reproductive isolation increases with phylogenetic distance between hybridizing species; (2) reproductive isolation is greater between sympatric than allopatric species with the same level of divergence; and (3) hybrid crosses conform to Haldane's rule. We tested for the existence of these patterns in ducks (subfamily Anatinae, sensu Livezey, 1997b) based on 1037 hybrids of known parentage. Our analyses of the number of interspecific crosses in relation to phylogenetic distance found a significant deviation between the observed and expected distribution of crosses controlling for the topology of the Anatinae phylogeny. In particular, we found both an excess of hybrid crosses among closely related species and a scarcity among distantly related species. The number of hybrid males also decreased with increasing phylogenetic distance between parental species, although the number of hybrid females remained low and constant. Sympatric species produced higher numbers of hybrid males than allopatric ones, despite no difference in phylogenetic distance among parental species in compared groups. The number of hybrid males exceeded the number of hybrid females, consistent with Haldane's rule. This was evident even though the analysis was restricted to a reduced set of phylogenetically independent crosses. However, the pattern was no longer significant after correction for the number of hybrid males by the male-biased sex ratio of adult ducks.